TINGKAT KERENTANAN MASYARAKAT TERHADAP PERUBAHAN IKLIM DI KECAMATAN XIII KOTO KAMPAR, PROVINSI RIAU - Insusanty, Enny; Ikhwan, Muhammad; Ervayenri, Ervayenri; Sadjati, Emy (Fakultas Kehutanan Universitas Lancang Kuning, 2020)
This research was conducted to determine the exposure, sensitivity and adaptation of the community in mitigating climate change and to obtain a map of the level of vulnerability of the community in mitigating climate change. This study uses secondary data and primary data with the survey method using a questionnaire of 75 respondents by purposive sampling which is a community in 3 (three) villages in District XIII Koto Kampar. In addition, in-depth interviews were conducted with village heads, farmer groups, community leaders and focus group discussions. Data processing is done by Excel, software Arc Gis 9.3 to obtain a map of the level of vulnerability of the community. Data analysis was carried out descriptively. The level of exposure and sensitivity of Pulau Gadang Village, Koto Mesjid and Tanjung Alai are included in the criteria of moderate. For the level of adaptation measured by the criteria of health, education, electricity and road infrastructure of Pulau Gadang Village and Koto Masjid, the criteria are rather high, while Tanjung Alai Village is of moderate criteria. The level of vulnerability in the three villages includes the level of moderate vulnerability